2016
DOI: 10.1103/physreva.94.021802
|View full text |Cite
|
Sign up to set email alerts
|

Near-resonant four-wave mixing of attosecond extreme-ultraviolet pulses with near-infrared pulses in neon: Detection of electronic coherences

Abstract: Coherent narrow band extreme ultraviolet (EUV) light is generated by a near-resonant four wave mixing (FWM) process between attosecond pulse trains and near infrared pulses in neon gas. The near-resonant FWM process involves one vacuum ultraviolet photon and two near-infrared (NIR) photons and produces new higher energy frequency components corresponding to the ns/nd to ground state (2s 2 2p 6) transitions in the neon atom. The EUV emission exhibits small angular divergence (2 mrad) and monotonically increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 35 publications
(39 reference statements)
3
53
0
Order By: Relevance
“…More generally, the investigation of the fast beatings shows the ability of T-REX to provide high-quality data for 2D spectroscopy. This scheme is conceptually similar to the XUV-IR four-wave mixing experiments recently demonstrated [21], and could be extended by using more sophisticated spatial and temporal combinations of excitation and probe pulses [22].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…More generally, the investigation of the fast beatings shows the ability of T-REX to provide high-quality data for 2D spectroscopy. This scheme is conceptually similar to the XUV-IR four-wave mixing experiments recently demonstrated [21], and could be extended by using more sophisticated spatial and temporal combinations of excitation and probe pulses [22].…”
mentioning
confidence: 96%
“…Pressure dependences have also been observed in absorption spectra and TRAX experiments. They have been interpreted as resulting from the reshaping of the propagating XUV exciting pulse by the strongly dispersive absorbing medium [21]. While these effects certainly have an influence in TRAX, they cannot be at play in T-REX which is based on multiphoton excitation by VIS pulses.…”
mentioning
confidence: 99%
“…In this paper, the dynamics of an XUV-excited vibronic wavepacket in a prototypical molecular system, H 2 , is explored. The recently developed method of XUV/near-infrared (NIR) four wave mixing spectroscopy [13][14]is applied to characterize the many pathways from the interaction of the NIR field with the XUV-excited state, probing such effects as laser-driven electronic-nuclear correlation and quantum coherence of the molecular wavepacket.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that by crossing an XUV attosecond pulse with a NIR laser pulse at a small angle, nonlinear XUV-NIR four wave mixing (FWM) from anatomic gas medium is observed at different emitting angles determined by the phase matching conditions [13]. Under such a non-collinear geometry, ultrafast XUV spectroscopy gains an additional dimension that is angle-resolved.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, femtosecond laser pulses have become effective tools in various fields including high-order harmonic generation (HHG) [1][2][3][4][5][6], strong-field ionization [6][7][8][9][10][11][12][13][14][15][16][17], and time-resolved spectroscopy [18][19][20][21][22][23][24] due to their ultrashort pulse duration and high peak intensity. Benefiting from the Kerr lens mode-locking (KLM) [25,26] and chirped pulse amplification (CPA) [27][28][29], the Ti:sapphire lasers have developed rapidly towards shorter pulse durations and higher pulse energies.…”
Section: Introductionmentioning
confidence: 99%